The Global Land Rush and the Arctic - Kröger, Antti Markus (2020)
This chapter discusses the recent Arctic land rush from the viewpoint of the larger literature on the global land rush and land grabbing, little of which has focused on the Arctic. This global view on the Arctic offers theoretical-methodological insights from a burgeoning literature on notable land control changes in different parts of the world (but not the Arctic) and can offer valuable knowledge on two key global/Arctic dimensions. Peer reviewed